"Illegal" by Association: Do Negative Stereotypes Divide or Unite Latinxs in the United States? . Issue 1 (4th July 2019) - Serrano‐Careaga, Jesús; Huo, Yuen J.
Abstract: In current American political discourse, individuals tend to mistakenly conflate being an undocumented immigrant with being Latinx. This conflation puts Latinxs who are legal residents or citizens (Latinx‐Americans) at risk of being negatively impacted by policies intended to deter undocumented immigrants. We examine whether being the target of anti‐immigration policies would lead Latinx‐Americans to politically engage on behalf of undocumented immigrants. Study 1 found that when Latinx‐Americans were led to believe that what happens to undocumented immigrants will affect them personally (linked fate), those who were primed with greater conflation of the two groups expressed more positive attitudes toward undocumented immigrants and other Latinxs. Study 2 found that this pattern of effects extended to the willingness to engage in collective action on behalf of undocumented immigrants. Study 2 also examined the role of emotions (anger and fear) in mediating the relationship between the conflation of Latinxs with undocumented immigrants and collective action intentions. Together, the findings shed light on how current immigration policies affect relations among key subgroups within the Latinx community and the conditions under which Latinx‐Americans will mobilize on behalf of undocumented immigrants.